Asymmetric synthesis of drugs and natural products - Nag, Ahindra (Boca Raton, FL CRC Press, 2018)
This book focuses on different techniques of asymmetric synthesis of important compounds, such as drugs and natural products. It gives insightful information on recent asymmetric synthesis by Inorganic, Organic and Enzymatic combinations. It also emphasizes chiral compounds and design of new catalyst for synthesis of compounds.--Provided by publisher.
Includes bibliographical references.
Keywords: Pharmaceutical chemistry; Asymmetric synthesis; Asymmetry (Chemistry); Drugs -- Synthesis; Organic compounds -- Synthesis